2014
DOI: 10.1016/j.appet.2013.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Using crowdsourcing to compare temporal, social temporal, and probability discounting among obese and non-obese individuals

Abstract: Previous research comparing obese and non-obese samples on the delayed discounting procedure has produced mixed results. The aim of the current study was to clarify these discrepant findings by comparing a variety of temporal discounting measures in a large sample of internet users (n = 1163) obtained from a crowdsourcing service, Amazon Mechanical Turk (AMT). Measures of temporal, social–temporal (a combination of standard and social temporal), and probability discounting were obtained. Significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 33 publications
6
89
0
Order By: Relevance
“…Third, our exploratory correlational analyses revealed a significant negative correlation between impulsivity measured by the MCQ and negative attitude towards obesity (AFA: dislike). Given that several previous studies showed positive correlations between BMI and MCQ (Bickel, et al, 2014; Borghans & Golsteyn, 2006; Ikeda, et al, 2010; Jarmolowicz, et al, 2014; Weller, et al, 2008), it might be partly related to a self-serving bias. Our study alone cannot provide a clear answer.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Third, our exploratory correlational analyses revealed a significant negative correlation between impulsivity measured by the MCQ and negative attitude towards obesity (AFA: dislike). Given that several previous studies showed positive correlations between BMI and MCQ (Bickel, et al, 2014; Borghans & Golsteyn, 2006; Ikeda, et al, 2010; Jarmolowicz, et al, 2014; Weller, et al, 2008), it might be partly related to a self-serving bias. Our study alone cannot provide a clear answer.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, scientific evidence is accumulating for the strong relation between temporal discounting and body mass. People carrying excess body weight, meaning those of greater body mass index (BMI), are more likely to choose smaller, more immediate monetary rewards (Bickel, et al, 2014; Borghans & Golsteyn, 2006; Ikeda, Kang, & Ohtake, 2010; Jarmolowicz, et al, 2014; Weller, Cook, Avsar, & Cox, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…mTurk has been used previously as a means to examine delay discounting in the obese (18). Exclusionary criteria were violating criteria for valid delay-discounting values on the delaydiscounting task (19), being a student, or receiving money from Virginia Tech through employment or for any other reason including study participation in the previous year.…”
Section: Participantsmentioning
confidence: 99%
“…To date, the relations between temporal discounting rate and body mass are mixed. Some studies show that people with higher body mass discount more rapidly than those with lower body mass (Ikeda et al, 2010; Borghans et al, 2006; Bickel et al, in press). This relation, however, is typically demonstrated only in females (Davis et al, 2010; Fields et al, 2013; Weller et al, 2008) and was absent in a number of other studies (Manwaring et al, 2011; Nederkoorn et al, 2006).…”
Section: Introductionmentioning
confidence: 99%